Multi - dimensional mechanism analysis of Choerospondias axillaris (Roxb.) Burtt et Hill in treating kidney stones: network pharmacology, molecular docking and in vitro experimental verification - Meiqi Qiu; Senhua Li; Yu Zhang; Jiaoxia Yan; Shiting Qin; Xijing Yin; Yujun Li; Chunhui Zeng; Ke Yang (Frontiers in Pharmacology)
Ethnopharmacological relevanceChoerospondias axillaris(Roxb.) Burtt et Hill (CA) is a medicinal and edible plant fruit with national characteristics in China. CA is commonly used in folk medicine for treating kidney diseases, heart diseases, and calming the mind. Modern pharmacological studies have demonstrated that CA exhibits effects such as protection against renal injury, antioxidation, anti-inflammation, and calcium antagonism.ObjectiveThis study aimed to explore the mechanism of CA in treating kidney stones through network pharmacology, molecular docking, and in vitro experiments.MethodsNetwork pharmacology was employed to screen the active components of CA. The targets of these active components and disease-related targets were predicted, and potential targets were obtained by taking the intersection of the two sets. The potential targets were then used to construct a Protein-Protein Interaction (PPI) network and the core targets were screened out. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted on the potential targets. A Drug-Component-Target-Pathway network was constructed. Molecular docking was carried out between key active ingredients and their corresponding core targets. Through the above methods, the mechanism of action of CA in treating kidney stones was preliminarily predicted. In addition, the effect of CA on the growth of Calcium Oxalate (CaOx) crystal was investigated in two-dimensional CaOx agar gel system. The protective effect of CA and its mechanism were explored in the model of Human Kidney Cortex (HKC) cell injury induced by Calcium Oxalate Monohydrate (COM) crystals.ResultsThrough network pharmacology analysis, 9 active ingredients were obtained, namely, (−)-taxifolin, naringenin, (−)-catechin, quercetin, bis [(2S)-2-ethylhexyl] benzene-1,2- dicarboxylate, (2R)-5,7-dihydroxy-2-(4-hydroxyphenyl) chroman-4- one, beta-sitosterol, ellagic acid, kaempferol. There were 272 protein targets for the active ingredients and 3,525 for diseases. After intersecting the two sets, 187 potential targets were identified. PPI network analysis revealed that the top five core targets were AKT1, IL6, TNF, TP53, and IL-1β. GO analysis indicated that the treatment of kidney stones with CA was involved in biological processes like the response to oxidative stress and regulation of inflammatory response. KEGG prediction suggested that the treatment of kidney stones with CA was closely associated with signaling pathways such as NF-κB and MAPK. Molecular docking results demonstrated that five key active ingredients (quercetin, kaempferol, (−)-catechin, β-sitosterol and naringenin) exhibited good binding ability with their corresponding core targets. The results of two-dimensional CaOx agar gel system showed that the CA-L group significantly decreased the aggregation of COM crystals. In the CA-M and CA-H groups, the crystals mainly existed in the form of Calcium Oxalate Dihydrate (COD), which was readily excreted with urine, causing minimal damage to renal epithelial cells. Moreover, the crystal surface area was significantly smaller compared that of the model group. CA could protect cells damaged by COM crystals by increasing SOD activity, reducing ROS levels, and decreasing lactate dehydrogenase (LDH) leakage. Simultaneously, CA downregulated the expression of inflammatory proteins such as NLRP3, Caspase-1, IL-1β, as well as the expression of OPN protein, which promotes crystal adhesion.ConclusionCA can attenuate the damage and adhesion of COM crystals to cells through multiple mechanisms. These include enhancing the cellular antioxidant capacity, regulating the activation of the NLRP3 inflammasome, reducing the expression of the crystal adhesion protein OPN, and preventing the further aggregation or mineralization of CaOx crystals. Thus, CA achieves the objective of treating kidney stones.